Effectiveness of structured teaching programme regarding polycystic ovarian syndrome among adolescent girls - John, Soniya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Polycystic ovary syndrome is an endocrine disorder that affects approximately 5% of all women. It occurs amongst all races and nationalities. It is the most common hormonal disorder among women of reproductive age and is a leading cause of infertility. As polycystic ovarian syndrome is an ovarian disorder marked by a lack of estrogen, hyperandrogenaemia, obesity, hyper insulinaemia and starts early in the adolescent period. So, we should teach them regarding the clinical features treatment and prevention. Methods: A quasi experimental one group pre-test post design was adopted to assess the effectiveness of structured teaching programme on knowledge regarding polycystic ovarian syndrome among adolescent girls, Bangalore. A sample of 60 adolescent girls was selected from NRI higher secondary school, Bangalore by purposive sampling technique. Collected data was analysed by using descriptive and inferential statistics. Results: More than half 54 (90.0%) were having inadequate knowledge and 6 (10%) were having moderate knowledge regarding PCOS before STP. Conclusions: Structured teaching programme was significantly effective in increasing the knowledge of polycystic ovarian syndrome. The most important role of the nurse is to provide awareness on prevention and health promotion.